Altered and allele-specific open chromatin landscape reveals epigenetic and genetic regulators of innate immunity in COVID-19 - Bowen Zhang; Zhenhua Zhang; Valerie A.C.M. Koeken; Saumya Kumar; Michelle Aillaud; Hsin-Chieh Tsay; Zhaoli Liu; Anke R.M. Kraft; Chai Fen Soon; Ivan Odak; Berislav Bošnjak; Anna Vlot; et al. (Elsevier, 2023)
Summary: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes severe COVID-19 in some patients and mild COVID-19 in others. Dysfunctional innate immune responses have been identified to contribute to COVID-19 severity, but the key regulators are still unknown. Here, we present an integrative single-cell multi-omics analysis of peripheral blood mononuclear cells from hospitalized and convalescent COVID-19 patients. In classical monocytes, we identified genes that were potentially regulated by differential chromatin accessibility. Then, sub-clustering and motif-enrichment analyses revealed disease condition-specific regulation by transcription factors and their targets, including an interaction between C/EBPs and a long-noncoding RNA LUCAT1, which we validated through loss-of-function experiments. Finally, we investigated genetic risk variants that exhibit allele-specific open chromatin (ASoC) in COVID-19 patients and identified a SNP rs6800484-C, which is associated with lower expression of CCR2 and may contribute to higher viral loads and higher risk of COVID-19 hospitalization. Altogether, our study highlights the diverse genetic and epigenetic regulators that contribute to COVID-19.